2013
DOI: 10.1038/nn.3397
|View full text |Cite
|
Sign up to set email alerts
|

Convergent cortical innervation of striatal projection neurons

Abstract: Anatomical studies have led to the assertion that intratelencephalic (IT) and pyramidal tract (PT) cortical neurons innervate different striatal projection neurons. To test this hypothesis, the responses of mouse striatal neurons to optogenetic activation of IT and PT axons were measured. Contrary to expectation, direct and indirect pathway striatal spiny projection neurons (SPNs) responded to both IT and PT activation, arguing that these cortical networks innervate both striatal projection neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
131
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(142 citation statements)
references
References 17 publications
(22 reference statements)
11
131
0
Order By: Relevance
“…I explored parameters of the model that best explain the experimental data for the PPR (Ding et al 2008) in the following ways. For the parameter optimization, I used the results of the recent optogenetic study by Kress et al (2013), introduced in the Introduction as a constraint. Specifically, the optogenetic study has shown that stimulation of IT axons evoked comparable responses in dMSNs and iMSNs (according to Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…I explored parameters of the model that best explain the experimental data for the PPR (Ding et al 2008) in the following ways. For the parameter optimization, I used the results of the recent optogenetic study by Kress et al (2013), introduced in the Introduction as a constraint. Specifically, the optogenetic study has shown that stimulation of IT axons evoked comparable responses in dMSNs and iMSNs (according to Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the connections between these distinct cell populations, anatomical studies have shown that IT and PT cells preferentially target dMSNs and iMSNs, respectively (Lei et al 2004;Reiner et al 2010). However, it has remained elusive whether IT and PT cells differentially activate dMSNs and iMSNs as suggested from the anatomical findings (see Ballion et al 2008;Reiner et al 2010).A recent study (Kress et al 2013) addressed this issue by using optogenetics and revealed that stimulation of IT axons evoked comparable responses in dMSNs and iMSNs and that stimulation of PT axons caused about twice larger responses in dMSNs than in iMSNs, apparently opposite to the anatomical suggestion. This study, however, applied only brief stimulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pyramidal cells with projections restricted to intratelencephalic (IT) targets have been classified as IT-type neurons and pyramidal neurons with projections beyond the telencephalon (i.e., corticospinal, corticotectal, corticopontine) have been classified as PT-type neurons (Catsman-Berrevoets et al 1980;Kress et al 2013;Reiner et al 2003Reiner et al , 2010Shepherd 2013). In rat somatosensory cortex, the vast majority of IT-type neurons are in layers 2/3 and layer 5A (Cowan and Wilson 1994;Molyneaux et al 2009;Reiner et al 2003Reiner et al , 2010Shepherd 2013;Wilson 1987).…”
Section: ϩmentioning
confidence: 99%
“…The existence of crossed cortico-striatal projections is well documented in the rodents (Carman et al 1965;Wilson 1987;Morishima and Kawaguchi 2006;Alloway et al 2009;Shepherd 2013) but somewhat neglected in primates (Lieu and Subramanian 2012). Given the current enhanced interest in the striatal and corticostriatal functions (Kress et al 2013;Smith and Graybiel 2013;Stephenson-Jones et al 2013;Znamenskiy and Zador 2013;Reig and Silberberg 2014) also related to their role in psychosis (Koch et al 2014;Burguière et al 2014;Nakamae et al 2014), we reinvestigated the crossed cortico-striatal connections using modern histological tract tracing in the monkey as well as diffusion tractography (DT) in monkeys and human. We describe a robust decussating callosal projection to the n caudatus and putamen, originating from prefrontal, premotor, and motor areas.…”
mentioning
confidence: 99%